Concept of Social Entrepreneurship Values in Pesantren Based on the Success Story of a Religious Social Entrepreneur - Furqonul Haq (Faculty of Islamic Economics and Business, Madura Islamic State University, 2025)
This study explores the core values and operational mechanisms of religious social entrepreneurship through the case of Sholah Al Athiyah in Tafahna Al Asyrof, Egypt. This research utilizes a qualitative approach through document analysis of biographical records of Sholah Al Athiyah's business journey. Based on the success story of Sholah Al Athiyah, the concept of social entrepreneurship values ​​in Islamic boarding schools consists of three elements. First, spiritual values: the